2023
DOI: 10.1097/prs.0000000000010947
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Combined Conjoint Fascial Sheath and Levator Muscle Composite Flap Suspension for Congenital Severe Ptosis

Abstract: Background: Conjoint fascial sheath (CFS) suspension has been gradually recognized and accepted for the treatment of congenital severe blepharoptosis in recent years. To address the problem of postoperative upper eyelid position regression of only CFS suspension, we designed and implemented a CFS combined Levator muscle (CFS+LM) complex flap. This research aims to analyze the surgical efficacy of CFS+LM and FMF suspension surgery. Methods: Patients diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Intraoperative or postoperative swelling or bleeding may also result in the prolapse of the superior fornix. 7 This study found that the BCVA (logMAR) was greater in the severe ptotic eyes than the nonseverely ptotic ones, which may indicate inferior visual acuity in the former. Severe congenital ptosis can result in amblyopia, which has a detrimental effect on BCVA.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Intraoperative or postoperative swelling or bleeding may also result in the prolapse of the superior fornix. 7 This study found that the BCVA (logMAR) was greater in the severe ptotic eyes than the nonseverely ptotic ones, which may indicate inferior visual acuity in the former. Severe congenital ptosis can result in amblyopia, which has a detrimental effect on BCVA.…”
Section: Discussionmentioning
confidence: 60%
“…17 Upper lid excursion was worse because the frontalis flap was less elastic than the LM, increasing the risk of lagophthalmos and closure insufficiency. 7 Thus, CFS suspension was born.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations